Immunochemical determination of cellular prion proteinin plasma from healthy subjects and patients withsporadic CJD or other neurologic diseases - Völkel, Dirk; Zimmermann, Klaus; Zerr, Inga; Bodemer, Monica; Lindner, Thomas; Turecek, Peter L.; Poser, Sigrid; Schwarz, Hans P. (Transfusion (Philadelphia, Pa.), 2001)
BACKGROUND: Creutzfeldt‐Jakob disease is thought to be caused by conversion of cellular prion protein (PrP) from its soluble form (PrPsen) to a pathologic form (PrPres). The occurrence of a new variant of CJD has increased the demand for a rapid assay capable of detecting a theoretical risk of transmission of the disease by blood or plasma. STUDY DESIGN AND METHODS: A quantitative sandwich ELISA for routine screening was developed for analysis of PrP levels in plasma. The time‐resolved dissociation‐enhanced fluorescence technology allowed a detection limit in plasma samples of approximately 50 pg/mL. Levels of PrPsen were tested in plasma from 31 patients with CJD, from 11 patients with other neurodegenerative diseases, and from a control group of 200 healthy subjects. RESULTS: The assay recognized both PrPsen and pathologic PrPres, but did not differentiate between the two isoforms. PrPsen levels were higher in plasma from both patient groups than in plasma from the control group: 27 of the 31 (87%) CJD patients and all patients with other neurodegenerative diseases had higher levels than the highest concentration found in the control group. No correlation was found between age and PrP level. No signal could be detected in the CJD samples after protease K digestion, indicating that all detected PrP was protease‐sensitive and therefore not pathologic. CONCLUSION: These data suggest that soluble PrPsen in plasma samples might be useful as a surrogate marker for a broad spectrum of neurologic diseases as well as for CJD.